Pesca artesanal marinha à vela na Região Metropolitana de Fortaleza, Ceará, no contexto dos Objetivos de Desenvolvimento Sustentável (ODS). - Andrade, João Angelo Peixoto de (2024)
The United Nations’ Ocean Science Decade for Sustainable Development stimulates oceans research in its interfaces with natural and social sciences highlighting the traditional knowledge as a pertinent source of data supporting the Agenda 2030 Sustainable Development Goals (SDGs). The artisanal fisheries, characterized by the low potential for generating negative socio-environmental impacts to biodiversity and marine ecosystems is consistent with the SDG 14 – Life Below Water among others, in this regard, this study starts from the hypothesis that artisanal fishermen’s Environmental Perception (EP) and Traditional Ecological Knowledge (TEK) along with the participation of Fishing Colonies in collecting socio-environmental and fishing data are relevant to SDGs supportive policies in the coastal municipalities facing the sea in Fortaleza’s Metropolitan Area. In that sense, this study overall objective consists in investigating the viability of creating an Artisanal Fishery Digital Data Network (AFDDN) in the aforementioned municipalities while the specific objectives consist of: register the EP and the TEK of artisanal fishermen; analyze the relevance of the artisanal fishermen EP and TEK to fishing and coastal management policies aligned with the SDGs; ascertain the willingness of fishing colonies to participate in socio-environmental and fishing data collection to integrate an AFDDN; and analyze the feasibility of including the EP and TEK in the AFDDN. The present study comprises a qualitative approach including bibliographic, documental and field research based on participant and unsystematic observation including techniques such as semi-structured interviews, photographic records and field notes. Data analysis involves the use of word clouds and the software Statistical Package for Social Sciences regarding the interviews and narratives of artisanal fishermen and fishing colonies’ managers. Results indicate the fishing colonies agreement to collect in-field data and to participate in the creation of an AFDDN as well as the relevance of EP and TEK as a pertinent source of information to subsidize Artisanal Fishing Management Policies as well as Integrated Coastal Zone Management aligned with the Agenda 2030 SDGs.